Analisis Tingkat Pelayanan Jaringan Jalan Di Kota Surakarta - Rahmawan, Agung, Dra. Hj. Umrotun, M.Si, Agus Anggoro Sigit, S.Si, M.Sc (2015)
Research about Analysis of Service Level Road Network is aiming to : 1) to analyze the extent to which the level of comfort this time and circumstances of Physical street in Surakarta, so it can been suggested that these roads are according to function, 2) to analyze the similarities and differences in the factors that affect the level the comfort of the road network in the city of Surakarta. The method used in this research is survey method with purposive sampling method .Data of samples taken at the time of the survey include the volume of vehicles, extensive measurement of the effective way. the calculation of the vehicle, the operator is placed in the middle of the road and on the both side edges of the road are observed. The Results of this study are 1) level of services the worst in the morning peak hour is Jend.Sudirman street, roads that have a good level of service traffic in the morning peak hour is the Major Sunaryo street. In the afternoon peak hour roads that have high levels of services the worst is Yos Sudarso street, while the roads at peak hours during the most excellent level of services are contained Major Sunaryo street. Level of service roads is at peak hours in the afternoon, roads that have high levels of services the worst is the Captain Mulyadi street and Sudirman street. Roads that have bettrer levels of services at peak hours afternoon that Major Sunaryo street, 2) factors that influence the service level is the level of road use, speed, density and barriers that occur